Distress intolerance moderation of motivated attention to cannabis and negative stimuli after induced stress among cannabis users: an ERP study. (7th May 2018) - Macatee, Richard J.; Okey, Sarah A.; Albanese, Brian J.; Schmidt, Norman B.; Cougle, Jesse R.
Abstract: Prevalence of cannabis use is increasing, but many regular users do not develop cannabis use disorder (CUD); thus, CUD risk identification among current users is vital for targeted intervention development. Existing data suggest that high distress intolerance (DI), an individual difference reflective of the ability to tolerate negative affect, may be linked to CUD, but no studies have tested possible neurophysiological mechanisms. Increased motivated attentional processing of cannabis and negative emotional stimuli as indexed by neurophysiology [i.e. the late positive potential (LPP)], particularly during acute stress, may contribute to CUD among high DI users. Frequent cannabis users with high ( n  = 61) and low DI ( n  = 44) viewed cannabis, negative, and matched neutral images during electroencephalography (EEG) recording before and after a laboratory stressor. Cannabis cue‐elicited modulation of the 1000‐ to 3000‐milliseconds LPP was larger in high DI users at post‐stressor only, although the effect was only robust in the 1000‐ to 2000‐milliseconds window. Further, modulation magnitude in the high DI group covaried with stress‐relief craving and some CUD indices in the 400‐ to 1000‐milliseconds and 1000‐ to 3000‐milliseconds windows, respectively. No significant effects of DI on negative stimuli‐elicited LPP modulation were found, although inverse associations with some CUD indices were observed. Finally, exploratory analyses revealed some evidence for DI moderation of the relation between subjective stressor reactivity and negative stimuli‐elicited LPP modulation such that greater stressor reactivity was associated with blunted versus enhanced modulation in the high and low DI groups, respectively. Negative and cannabis stimuli‐elicited LPP modulation appear to index distinct, CUD‐relevant neural processes in high DI cannabis users. Abstract : We evaluated motivated attentional processing of cannabis and negative emotional stimuli as indexed by neurophysiology [i.e. the late positive potential (LPP)] before and after acute stress in regular cannabis users reporting high versus low distress intolerance, an individual difference linked to cannabis use disorder (CUD). High distress intolerance cannabis users demonstrated enhanced post‐stressor cannabis cue‐elicited, sustained LPP modulation, which was associated with some CUD indices. Negative and cannabis stimuli‐elicited LPP modulation appears to index distinct, CUD‐relevant neural processes.